2018
DOI: 10.3390/w10101357
|View full text |Cite
|
Sign up to set email alerts
|

Flood Vulnerability, Environmental Land Use Conflicts, and Conservation of Soil and Water: A Study in the Batatais SP Municipality, Brazil

Abstract: In many regions across the planet, flood events are now more frequent and intense because of climate change and improper land use, resulting in risks to the population. However, the procedures to accurately determine the areas at risk in regions influenced by inadequate land uses are still inefficient. In rural watersheds, inadequate uses occur when actual uses deviate from land capability, and are termed environmental land use conflicts. To overcome the difficulty to evaluate flood vulnerability under these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 57 publications
0
18
0
5
Order By: Relevance
“…The starting step comprises the identification and mapping of recharge areas, but this phase has not commenced. It is worth reinforcing that the inadequate use of recharge zones can reduce water infiltration in the soil through waterproofing and compaction; and low infiltration rates can concentrate and increase surface runoff, generating problems in urban centers such as flooding [39][40][41][42][43]. In addition, the intense exploitation of water resources in urban areas can generate water scarcity and even depletion [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…The starting step comprises the identification and mapping of recharge areas, but this phase has not commenced. It is worth reinforcing that the inadequate use of recharge zones can reduce water infiltration in the soil through waterproofing and compaction; and low infiltration rates can concentrate and increase surface runoff, generating problems in urban centers such as flooding [39][40][41][42][43]. In addition, the intense exploitation of water resources in urban areas can generate water scarcity and even depletion [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Another seven points were added (Figure 4a and b) which also validate SWMM maps. This approach is suggested as a way to manage the lack of validation data in studies [62]. However, an in-depth study is suggested for further research in order to collect more information about flooding episodes in different return periods.…”
Section: Without Suds Strategiesmentioning
confidence: 99%
“…As informações geradas, a partir de mapas temáticos obtidos por técnicas de geoprocessamento para o ordenamento do território são inúmeras, tais como: formações básicas do relevo, hidrografia, características geológicas, geomorfológicas, declividades ou áreas de ocorrências de doenças e área de expansão urbana, análise de infraestrutura, informações socioeconômicas, plano diretor, lei de uso e ocupação do solo, zoneamento, análises e mapeamento de riscos ambientais (Caldas, 2018;Camâra et al, 1996).…”
Section: Introductionunclassified